Bilingualism Essential for Evolution of Our Laws and Access to Justice for English and French-speaking Minority Communities - Quebec Community Groups Network (QCGN) (2015)

Youth Development Initiatives - Coasters Association (2015)
The Coasters Association has had many achievements over the years regarding youth initiatives, and priority areas have been identified. These achievements have contributed to the development and vitality of the region’s communities; however, there are many challenges that remain to hinder the future development and sustainability of the region.

Partnering for the Well-being of Minority English-Language Youth, Schools & Communities - Gonsalves, Allison; Kueber, Russell; Langevin, Paule; Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2015)
This document identifies some of the unique challenges, strengths, and aspirations of English-speaking youth in Quebec and provides a school and community-based framework for action intended to have a positive impact on their well-being and educational success. It emerges from the collaboration of community health and social services networks, called (NPIs) - abbreviation for the Networking and Partnership Initiative and Community Learning Centers (CLCs) seeking to improve the overall well-being of minority language youth residing in province.
Parallel title: School & Community Resources - Working Together is the Key!
Keywords: Official Language Minority Community (OLMC)

QFHSA News - Quebec Federation of Home and School Associations (QFHSA) (2015)
Number of pages: 24